1984
DOI: 10.3109/14017438409099383
|View full text |Cite
|
Sign up to set email alerts
|

Combined Valve Replacement and Myocardial Revascularization: Factors Influencing Early and Late Results

Abstract: The risk factors involved in simultaneous valve replacement and coronary artery bypass grafting were evaluated in 54 consecutive patients, 42 men and 12 women, aged 22 to 73 years. The predominant valve anomalies were aortic stenosis (30 patients), aortic regurgitation (9), mitral regurgitation (10) and mitral stenosis (5). All the patients had angina. Myocardial infarction had occurred in 22 cases and was impending at the time of operation in 10. The diseased valves were replaced with mechanical prostheses, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Current guidelines recommend bypass of all significant stenoses at the time of AVR, with evidence level C (4); however, addition of coronary artery bypass grafting (CABG) to AVR is associated with elevated short- and long-term mortality (5–10). This association may be causal (e.g., by increasing myocardial ischemic time (11)) or simply a marker for a high-risk patient profile. Clarifying this may lead to more targeted diagnostics, therapy, and chronic disease management.…”
Section: Introductionmentioning
confidence: 99%
“…Current guidelines recommend bypass of all significant stenoses at the time of AVR, with evidence level C (4); however, addition of coronary artery bypass grafting (CABG) to AVR is associated with elevated short- and long-term mortality (5–10). This association may be causal (e.g., by increasing myocardial ischemic time (11)) or simply a marker for a high-risk patient profile. Clarifying this may lead to more targeted diagnostics, therapy, and chronic disease management.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the outcomes of patients undergoing combined CABG and AVR. Although combined myocardial revascularization and AVR increases cross-clamp time 1036 and has the potential to increase perioperative myocardial infarction and early postoperative mortality compared with patients without CAD undergoing isolated AVR, [1037][1038][1039][1040] in several series, combined CABG has had little or no adverse effect on operative mortality. [1041][1042][1043][1044][1045][1046][1047] Moreover, combined CABG and AVR reduces the rates of perioperative myocardial infarction, operative mortality, and late mortality and morbidity compared with patients with significant CAD who do not undergo revascularization at the time of AVR.…”
Section: Diagnosis Of Coronary Arterymentioning
confidence: 99%